Pengembangan Aplikasi Cerdas Untuk Pendukung Keputusan Pemilihan Saham Potensial Bagi Investor Pemula - Veri Ilhadi; Ilham Sahputra; Sujacka Retno; Siti Fatimatun Zahro; Irvan Na’syakban (E-Jurnal Universitas Samudra, 2025)
This study develops an intelligent application to support decision-making in selecting potential stocks for novice investors. Stock selection is often a challenge for beginner investors due to limited experience, analytical skills, and understanding of a company's fundamental indicators. The developed Decision Support System (DSS) integrates two multi-criteria analysis methods: AHP (Analytic Hierarchy Process) and VIKOR (VIšekriterijumsko KOmpromisno Rangiranje). AHP is employed to systematically determine the criteria weights based on user preferences, addressing VIKOR’s limitation in subjective weight assignment. VIKOR is then used to rank stocks by identifying the best compromise solution. The application is user-friendly and utilizes eight fundamental indicators: PER, PBV, ROA, ROE, EPS, BVPS, DR, and DY. Functional testing using the black-box testing method showed that all application features work properly. Recommendation validation also confirmed that the application provides accurate suggestions, consistent with manual analysis using the AHP-VIKOR model.